Interpersonal synchrony affects performers’ sense of agency - Reddish, P; Tong, E; Jong, J; Whitehouse, H (Routledge, 2019)
We investigated if interpersonal synchrony can lead to a sense of agency over another’s movement (extended self-agency). In Experiment 1, we found that extended self-agency was greater during synchrony than asynchrony. However, we also found that synchrony boosted participants’ sense that the other performer had agency over their actions (extended other-agency). This finding may have been because synchrony created a sense of distributed agency. If so, then manipulating the degree of influence participants have over their partner’s behavior should boost extended self-agency when leading and extended other-agency when following. Experiment 2 confirmed these predictions. We also found synchrony created a sense of joint-agency. These results show how interpersonal synchrony can modulate a core aspect of the self.